(untitled) - Williams, Lewis (Studia Bioethica, 2015)
As currently articulated, bio-ethics and human rights are concerned with interventions that affect human beings in more or less direct ways. Moral and ethical reasoning therefore, focus on the primacy of life processes pertaining to human wellbeing. This article argues the potential of human ecology, as a philosophical and scientific endeavour to reposition humanities embeddedness in nature as the primary informant of a relational ethic for bio-medical and technological innovations aimed at enhancing human well-being. It emphasises the potential of place-based thought and other than human agency as being key to this endeavour. In contrasting Positivist/modernist, Participatory and Indigenous approaches to human ecology the significance of the political and economic dimensions of ecology in mediating dynamics of power, culture, place and nature is demonstrated. Drawing on the example of a participatory research project with Indigenous, migrant and refugee women (who under the Universal Declaration for Bio-ethics and Human Rights are considered vulnerable populations), the human ecology concept of social-ecological resilience is applied to the cultural political - ecological dimensions of these communities. It is argued that the subjugation of non-Western knowledge systems and cultures and the associated concept of other than human agency endangers human life, possibly in time rendering the Declaration in its present expression irrelevant.